(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This annotation checks for set expressions. Set expressions can also be categorized based on their complexity: This involves classifying set expressions according to the level of difficulty in terms of the operations involved (e.g., union, intersection, complement) and the number of elements in the sets. Additionally, set expressions can be classified based on their purpose: This includes grouping set expressions according to their specific application or function, such as in mathematics, computer science, linguistics, or any other domain where sets are used.